Type specimens of the traditional Myrmicinae (Hymenoptera: Formicidae) ant tribes deposited in the Museu de Zoologia da Universidade de São Paulo, Brazil: Adelomyrmecini, Basicerotini, Blepharidatt ini, Crematogastrini, Formicoxenini, Lenomyrmecini, Myrmicini, Phalacromyrmecini, Pheidolini, Stegomyrmecini, Stenammini and Tetramoriini - Ulysséa, Mônica Antunes; Prado, Lívia P.; Brandão, Carlos Roberto F. (Papéis Avulsos de Zoologia, 2015)
The present catalogue lists ant types of 12 traditional Myrmicinae ant tribes (Adelomyrmecini, Basicerotini, Blepharidattini, Crematogastrini, Formicoxenini, Lenomyrmecini, Myrmicini, Phalacromyrmecini, Pheidolini, Stegomyrmecini, Stenammini and Tetramoriini) housed in the Formicidae Collection of the Hymenoptera Laboratory, Museu de Zoologia da Universidade de São Paulo (MZSP), Brazil, completing the publication of Myrmicinae types deposited in this institution. We adopted the traditional classification for Myrmicinae tribes to follow the already published catalogues regarding the Attini, Cephalotini, Dacetini and Solenopsidini and published catalogues in this series. In total, the present catalogue includes types of 213 nominal species, of which 169 are still valid. Twelve species listed here are represented by holotypes only, 28 by holotypes and paratypes, 102 species by paratypes only, 65 species by syntypes, and five species by lectotypes and paralectotypes. We record the label information, morphological condition of the specimens, nomenclatural changes, and type status, following the recommendations of the International Code of Zoological Nomenclature (ICZN).